Improving Scientific Judgments in Law and Government: A Field Experiment of Patent Peer Review. Issue 2 (22nd May 2020) - Ho, Daniel E.; Ouellette, Lisa Larrimore
Abstract : Many have advocated for the expansion of peer review to improve scientific judgments in law and public policy. One such test case is the patent examination process, with numerous commentators arguing that scientific peer review can solve informational deficits in patent determinations. We present results from a novel randomized field experiment, carried out over the course of three years, in which 336 prominent scientific experts agreed to provide input on U.S. patent applications. Their input was edited for compliance with submission requirements and submitted to the U.S. Patent and Trademark Office (USPTO) by our research team. We show that the intervention caused examiners to (1) increase search efforts and citations to the non‐patent (scientific) literature and (2) grant the application at lower rates in the first instance. However, results were substantially weaker and resource costs substantially higher than anticipated in the literature, highlighting significant challenges and questions of institutional design in bringing scientific expertise into law and government.